Аналитическая модель и расчет рейтинговой оценки нитридборных сверхтвердых композитов - Гуцаленко, Юрий Григорьевич (НТУ "ХПИ", 2014)
Рассматривается проблема сравнения эксплуатационных возможностей инструментальных материалов в условиях использования каждого из них в своей рекомендуемой области и в своей системе нормативных режимов резания и нормативной стойкости. Предложена аналитическая модель и выполнен расчет рейтинговой оценки для стандартной группы сверхтвердых композитов на основе кубического нитрида бора.

The problem of comparing the operational capabilities of the tool materials in the conditions of use of each of them in their recommended area and its system of standard cutting conditions and regulatory stability is considered. Development is based on the database of the conditions and tool life norms for tests of the superhard materials under regulations the interstate standard 28762-90 that is applied in Ukraine. An analytical model and the calculation are made for the rating of the standard group of superhard composites based on cubic boron nitride. Preference for the proposed model as a reflection of adopted technological ideology is determined by amount (volume) of removed material for the cutting tool life. The highest rating is determined by the maximum material removal. The calculations on the model established the superiority of Tomal-10 composite over others. In the context of the research motive this composite is proposed as a base superhard boron nitride to develop an expert system for forecasting roughness on difficult to machine materials after diamond-spark grinding. The expert system is created in Ukraine within the framework of tasks for state research project 0113U000425.
Analytical model and the calculation of rating estimation for superhard boron nitride composites
Keywords: кубический нитрид бора; эксплуатационные возможности; инструментальные материалы; superhard composites; operational capabilities; rating estimation